The Increasing Tendency of Nepalese Youth to go Abroad for Education and Work: Sine Qua Non of State Policy, Entrepreneurship, and Local Skills and Ability - Shrestha, Shyam Sundar; Ojha, Sateesh Kumar (SADGAMAYA, 2025)
This article aims to develop insights into the situation that how an independent, socially and economically sound country turns into a dependent and socially and economically weak country. The method adopted is a review of the literature. The finding is the interplay of weak central government policy, weak entrepreneurship, and low-level skills in the field.